Francophonie et identités culturelles - Albert, Christiane (Karthala, 1999)
L'expression littéraire est un acte puissant par lequel un être construit son identité à la fois individuellement et collectivement. Dans le contexte de la francophonie, cet acte identitaire est d'autant plus paradoxal que la langue utilisée est le français et que la littérature francophone émerge, lors de la colonisation, dans un environnement multiculturel, à partir de la déconstruction d'une littérature dominante. Afin d'interroger les multiples processus intervenant dans la constitution de l'identité francophone, un colloque a eu lieu à l'université de Pau en 1998. Il s'est achevé par une table ronde qui a réuni trois écrivains francophones : Rachid Boudjedra, Pius Ngandu Nkaashama et Tierno Monénembo qui ont évoqué la relation qu'ils entretiennent avec la langue et l'écriture. Cet ouvrage rassemble les interventions des participants à ce colloque. Tout au long de ces journées, l'identité francophone est apparue comme une configuration d'éléments multiples où la langue remplit une fonction importante. Elle ne suffit cependant pas à fonder le discours identitaire dans la mesure où elle n'est qu'un isntrument au service des écrivains. D'autres éléments apparaissent, en effet, déterminants dans l'élaboration de cette identité, éléments indissociables de l'Histoire et des développements propres à chaque société. De ce fait, l'espace littéraire francophone apparaît décentré par rapport à la langue française car il fait entendre de nouvelles voix à la périphérie de l'aire linguistique du français. Ce qui démontre, si cela était nécessaire, la richesse et la complexité de la littérature francophone, qui constitue d'une certaine façon, le laboratoire de la culture post-moderne du vingt-et-unième siècle.
Keywords: 1800-1899; 1900-1999; afrique; approches et analyses; colonialisme; cours; discipline; fem1000; francophonie; haïti; identités culturelles; langage; postcolonialisme; postmodernisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; violences; études littéraires

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences